Consumer preference and willingness to pay for sheep meat quality and safety in Addis Ababa - Neme, A. (Haramaya University, 2011)
The main objective of this study was to assess consumer preference and willingness to pay for sheep meat quality and safety attributes in Addis Ababa city. Two hundred (200) households were selected using multi-stage sampling procedure. Rapid market appraisal and key-informant discussions were held to select five most relevant sheep meat quality and safety attributes i.e. hygiene, freshness, official stamp, fat content, and price. These were derived using an orthogonal fractional factorial design to create profile scenarios. A cross-tabulation analysis was also employed between socio-demographic features and consumption frequency. The results of cross tabulation analysis indicated that sociodemographic variables such as age, education level, occupation, and household income have a significant effect on consumer preference. However, demographic variables such as gender, religion, ethnicity, and marital status do not. The data from conjoint experiment were estimated using rank-ordered logit model in which the ranking of product profile were determined by the five quality and safety attributes. Relative importance and willingness to pay for were estimated from the coefficient of rank-ordered logit result. All parameters from rank-ordered logit model were significantly different from zero with the expected signs, suggesting that the quality and safety attributes selected significantly influence consumer choice behavior at 1% significance level. The result of the analysis indicates that hygiene is highly valued by all consumers regardless of income strata, as indicated by part-worth utility, relative importance, and willingness to pay and the least preferred attribute is fat content. Hygiene contributes up to 37.41% of overall utility, followed by freshness (18.48%), price (16.02%), official stamp (14.29%), and fat content (13.80%). From these results, the most preferred combination of sheep meat quality and safety attributes was clean, fresh, price of 42 ETB, official stamp present, and low fat content. Result from this study indicates that respondents from high income households were more concerned about hygiene and fat content than medium and low income households. Conversely, respondents from the low income households were more concerned about price, freshness and official stamp than their medium and higher income counterparts. It was also found that consumers have a particular preference for hygiene as the most dominant attribute influencing purchasing decision. A large percent of consumers were willing to pay a premium for hygiene; where individual consumers were willing to pay a premium of 23.35 ETB for sheep meat of better and improved cleanliness. Freshness was ranked second with a WTP premium of 11.53 ETB for freshness attribute in sheep meat. On average, consumers WTP for official stamp, and fat content were 8.92 ETB and 8.61 ETB respectively. Thus, from the WTP result, hygiene, freshness, official stamp, and fat content were ranked from most to least valued attributes, thus preferred in terms of how their levels influencing consumer preference. The derived WTPs across income strata were also similar with those obtained using the whole sample. This finding would have a positive implication for forming product differentiation strategies within the animal source food policy in general and the sheep meat industry in particular. Specifically, it could be a source of information for producers in the sheep meat industry about consumer preference and willingness to pay for the selected quality and safety attributes.